St. Lucia : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1997)
This paper reviews economic developments in St. Lucia during 1990-95. During 1991-92, economic growth slowed to an average of 5 percent (from 9 percent achieved in the late 1980s) as banana production stagnated, and in spite of strong growth of construction and tourism. In 1993-94, real GDP growth fell further to an annual average of 2 percent reflecting a severe drop in banana production associated with the 1993 drought and the 1994 tropical storm. In 1995 and the first part of 1996, growth rebounded to an annual average of about 4 percent.